Mental Adaptation to Capsule Work During COVID-19 Outbreak: The Case of Israeli Air Force Career Personnel. Issue 1 (30th January 2021) - Gordon, Shirley; Garbi, Dror; Ben Bassat, Shahar; Shapira, Shachar; Shelef, Leah
ABSTRACT: Objective: Dealing with the COVID-19 outbreak required a rapid adjustment to an unfamiliar and unique situation. The current study aimed to identify the challenges faced by Israeli Air Force (IAF) career personnel. Method: A survey was conducted on 550 participants during the first wave of the COVID-19 outbreak. The participants completed a questionnaire that dealt with unique challenges (personal, family, and command). Results: Of 550 respondents, 54% reported low mood and irritability, 44% reported a constant feeling of anxiety, and 29% reported having sleep problems. Most of them (66%) were mainly concerned about infecting their family. The shift from normal work conditions to an unfamiliar capsule configuration concerned 58% of respondents. Functional continuity concerned 55% of respondents. Managing subordinates concerned 50% of the participants. Of the three types of challenges analyzed (personal, family, and command), the command challenge was the only one where the personal variables (military role, rank, and marital status) made no difference. Finally, about 30% of all respondents reported they needed professional support in dealing with the new circumstances. Their preferred platform was an easily accessible hotline. Conclusions: Life under the COVID-19 threat increased stress factors in the military career population. While reporting greater challenges and higher levels of stress, most of the respondents preferred a brief, focused consultation adjusted to the situation rather than conventional psychological help. The command challenge and the perceived responsibility stood above and beyond all variables examined in the present study.